Saccadic Behavior during the Response to Pure Vergence Stimuli I: General Properties (Journal of Eye Movement Research, 2007)
If two targets are carefully aligned so that they fall along the cyclopean axis, the required eye movement will be symmetrical with the two eyes turning equally inward or outward. When such “pure vergence stimuli” are used only a “pure vergence movement” is required, yet almost all responses include saccadic eye movements, a rapid tandem movement of the eyes. When saccades occur, they must either produce an error in the desired symmetrical response or correct an error from an asymmetrical vergence response. A series of eye movement responses to pure convergence stimuli (4.0 deg step stimuli) were measured in 12 subjects and the occurrence, timing and amplitude of saccades was measured. Early saccades (within 400 msec of the stimulus onset) appeared in 80% to 100% of the responses. In most subjects, the first saccade increased the asymmetry of the response, taking the eyes away from the midline position. In three subjects, these asymmetry-inducing saccades brought one eye, the preferred or dominant eye, close to the target, but in the other subjects these asymmetry-inducing saccades were probably due to the distraction caused by the transient diplopic image generated by a pure vergence stimulus. While many of these asymmetry-inducing saccades showed saccade-like enhancements of vergence, they were, with the exception of two subjects, primarily divergent and did not facilitate the ongoing convergence movement. All subjects had some responses where the first saccade improved response symmetry, correcting an asymmetry brought about by unequal vergence movements in the two eyes. In five subjects, large symmetry-inducing saccades corrected an asymmetrical vergence response, bringing the eyes back to the midline (to within a few tenths of a degree).